Universal scaling laws for metallic wrinkling on soft spherical substrates. (1st January 2021) - Yuan, Haozhi; Wu, Kai; Wang, Yaqiang; Zhang, Jinyu; Liu, Gang; Sun, Jun
Abstract : The surface wrinkling of metal films on spherical polydimethylsiloxane (PDMS) substrates was induced by thermal contraction. A novel scaling law among wrinkle wavelength, film thickness, and substrate radius was discovered experimentally and rationalized theoretically, with scaling exponent being constant and coefficient being material-dependent. The theoretical predictions agree well with the existing experimental data of other spherical shell/core systems, with shell/core modulus ratio spanning several orders of magnitude, indicative of the universality and robustness. The results shed new light on the wrinkling phenomenon of spherical surfaces and demonstrate a predictive pathway to create wrinkling patterns on demand. Graphical abstract: Image, graphical abstract